2002
DOI: 10.1037/0021-9010.87.6.1183
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effects of employee tenure on the relation between organizational commitment and job performance: A meta-analysis.

Abstract: This meta-analysis investigated the correlation between attitudinal commitment and job performance for 3,630 employees obtained from 27 independent studies across various levels of employee tenure. Controlling for employee age and other nuisance variables, the authors found that tenure had a very strong nonlinear moderating effect on the commitment-performance correlation, with correlations tending to decrease exponentially with increasing tenure. These findings do not appear to be the result of differences ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
245
3
15

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(291 citation statements)
references
References 75 publications
19
245
3
15
Order By: Relevance
“…However, other researchers have found that longevity at the workplace does not necessarily bring loyalty, commitment and indicate job satisfaction (e.g., Wright and Bonett [25] and Kass, Vodanovich and Callender [29]). Kass et al found a positive association between job dissatisfaction, boredom, and organizational tenure; they argued that longevity was due to workers being tied to their workplaces and lacking suitable job alternatives [29].…”
Section: Work Experience In the Accident And Safety Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, other researchers have found that longevity at the workplace does not necessarily bring loyalty, commitment and indicate job satisfaction (e.g., Wright and Bonett [25] and Kass, Vodanovich and Callender [29]). Kass et al found a positive association between job dissatisfaction, boredom, and organizational tenure; they argued that longevity was due to workers being tied to their workplaces and lacking suitable job alternatives [29].…”
Section: Work Experience In the Accident And Safety Literaturementioning
confidence: 99%
“…Much of the theoretical and empirical research has investigated the association between organizational tenure and job satisfaction, and the conclusions drawn have been deduced from the affective organizational attachment that develops with tenure (e.g., Ambrose and Cropanzano [24] and Wright and Bonett [25]). Through this link, work experience has been found to be a strong predictor of job satisfaction (e.g., Trevor [26] and Carsten and Spector [27]).…”
Section: Work Experience In the Accident And Safety Literaturementioning
confidence: 99%
“…As employees with lower organizational tenure are less familiar with the organization, they often enjoy a "honeymoon period" and tend to be more curious and enthusiastic about the new work environments (Helmreich, Sawin, & Carsrud, 1986;Wright & Bonett, 2002;Huang, Shi, Zhang, & Cheung, 2006). However, for employees with higher organizational tenure, as they have already got familiar with the responsibilities and tasks in their organizations, if they are not delegated to important tasks, they will be more likely to feel overqualified for their work.…”
Section: The Moderation Role Of Organizational Tenurementioning
confidence: 99%
“…Com efeito, na literatura de carreira e de comportamento organizacional, tempo de organização pode ser aferido como variável métrica em anos (Gibson & Lawrence, 2010) ou como variável não métrica que indica a fase da carreira na atual organização (Cohen, 1991;Jans, 1989;Ng & Feldman, 2011;Wright & Bonett, 2002). No último caso, as fronteiras que balizam os estágios variam entre as pesquisas, porém, o uso de intervalos de cinco anos está entre as opções mais frequentes (Ng & Feldman, 2011;Wright & Bonett, 2002).…”
Section: Tempo De Organização E Expectativas De Carreiraunclassified
“…No último caso, as fronteiras que balizam os estágios variam entre as pesquisas, porém, o uso de intervalos de cinco anos está entre as opções mais frequentes (Ng & Feldman, 2011;Wright & Bonett, 2002).…”
Section: Tempo De Organização E Expectativas De Carreiraunclassified